2020
DOI: 10.20956/jiks.v5i2.8934
|View full text |Cite
|
Sign up to set email alerts
|

The Mangrove Ecosystem Potential for Educational Tour Development Around Pond Education of Hasanuddin University (Unhas) in Mallusetasi District, Barru Regency.

Abstract: This research was conducted in October 2017. The research location was the Hasanuddin University Education Pond, Bojo Village, Mallusetasi District, Barru Regency. The objectives of this study were: (a) To identify the various types of mangroves that make up the educational field in the Hasanuddin University Education Pond; (b) To Identify and to recognize the organisms associated with various types of mangroves that compose educational sites on the coast of the UNHAS Education Pond, and (c) To analyze data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…This fungus has thin-walled conidiophores. (Saru, et al, 2019) and in Rote Ndao, East Nusa Tenggara, 11 species were found (Ngoma, et al, 2020). It provides an opportunity to utilize mangrove species for treatment, for example as an antibacterial.…”
Section: Testing the Antibacterial Activity Of Mangrove Endophytic Fungi Againstmentioning
confidence: 99%
“…This fungus has thin-walled conidiophores. (Saru, et al, 2019) and in Rote Ndao, East Nusa Tenggara, 11 species were found (Ngoma, et al, 2020). It provides an opportunity to utilize mangrove species for treatment, for example as an antibacterial.…”
Section: Testing the Antibacterial Activity Of Mangrove Endophytic Fungi Againstmentioning
confidence: 99%
“…Sonneratia alba merupakan penyusun hutan mangrove yang berfungsi sebagai perlindungan pantai dari badai dan ombak yang besar (Giesen et al 2006). Mangrove juga dapat menciptakan habitat yang produktif sehingga memiliki nilai ekonomis yang tinggi, misalnya sebagai tempat berpijahnya ikan, kerang dan udang (Giesen et al 2006;Saru et al 2019) dan organisme bentos (Aunurohim et al 2015). Fungsi vegetasi mangrove yang lain adalah sebagai penghasil bahan-bahan obat (Giesen et al 2006).…”
Section: Pendahuluanunclassified
“…The mangrove ecosystems that lies in the are can contribute positively to carbon absorption capabilities and countermeasures to the rate of global climate change, including the ecological dynamics of an ecosystem. Besides, mangrove ecosystems also ecologically serve as stability or balance of ecosystems, nutrient sources, nursery ground, feeding ground, and spawning ground [1] [2]. Benthos are organisms that live at the bottom of the water.…”
Section: Introductionmentioning
confidence: 99%